'Connor's communist control polities': why ethno‐federalism does not explain the break‐up of the Soviet Union, Yugoslavia and Czechoslovakia. Issue 3 (9th August 2018) - McGarry, John
Abstract: When the Soviet Union, Yugoslavia and Czechoslovakia broke apart, several prominent academics argued that this was because they were federations (or 'ethno‐federations' as they put it). This article uses Walker Connor's magnum opus on Marxist–Leninist strategy and practice in communist states to show the flaws in these analyses. Connor's work shows that it is more plausible to link the fate of the three communist states to their anti‐federalist practices than to the fact that they were formally federal.